IMPLEMENTASI METODE PEMBELAJARAN INTERAKTIF DALAM MENINGKATKAN PEMAHAMAN KONSEP AGAMA ISLAM DI KALANGAN PELAJAR SMA INTEGRAL RAHMATULLAH TOLITOLI - Rana Mufidah (UNISAN JURNAL, 2024)
This research aims to evaluate the effectiveness of implementing interactive learning methods in increasing understanding of Islamic religious concepts among Rahmatullah Tolitoli Integral High School students. Using a quasi-experimental design, data was collected from two groups of students: an experimental group that took part in interactive learning and a control group that took part in conventional learning methods. The results of the test for understanding Islamic religious concepts are used as the main indicator to evaluate the impact of the two learning approaches. Apart from that, students' perceptions of interactive learning were also observed through questionnaires. The results of the research show that the implementation of interactive learning methods significantly increases understanding of Islamic religious concepts among Rahmatullah Tolitoli Integral High School students. These findings have important implications for the development of Islamic religious education in high schools and provide guidance for the use of interactive learning methods in the context of Islamic religious education.